(untitled) (Педагогіка вищої та середньої школи, 2022)
Methodology of a fram ing game is consiolered. It has been shown, that successfully organijed games influence the improvement of knowledge qualify, skills and habits of pupils, the olevelopment of their activities, theformation o f their responsible attitudes to the process of learning.